Mathematical, nutritional and didactical principles of using 3 × 3 equations with Excel for the formulation of balanced feeds and rations for animals: Principios matemáticos, nutricionales y didácticos del uso de ecuaciones 3 × 3 con Excel en la formulación de alimentos balanceados y de raciones para animales - Santana Pérez , Angel Arturo (2023)
The use of different mathematical methods during the process of animal ration and concentrates formulation demands integral skills on animal nutrition, mathematics and didactical abilities during teaching of such methods at the institutions where agricultural careers are taught. This article aims to demonstrate howto integrate such capabilities, specifically on the use of 3×3equations and to motivate using Excel for that purpose. From the nutritional point of view, it is described how to consider the exactitudes on the nutritive value of each feed in 3×3system of equations in order to fit the amount and/or proportion of three nutrients to their animal requirements. It was also demonstrated the mathematical possibilities of 3 ×3 system of equations to solve diet formulation for animals, how to formulate them with Excel by those dealing with animal feeding. Didactically, it was noticeable that two examples of real and practical problems for teaching 3 × 3systems of equations were given.